Amelioration of Diabetes Associated Hypo-testicular Co-morbidities in Rat by Aloe vera (L.): Potent Extract Selection Study (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The experiment was framed to get the most effective extract of Aloe vera (L.) leaf gel for the amelioration of hypo-functional activity of testis in diabetic model rats. Only one frequency of streptozotocin was injected through skeletal muscle at 40 mg/kg body weight for diabetes induction. Treatment with aqueous or ethanol or methanol or hydro-ethanol (40:60) or hydro-methanol (40:60) extract of Aloe vera (L.) was continued for 28 days. Rats were euthanized and sacrificed on 29th day. Fasting blood glucose level, kinetics of hexokinase, androgenic key enzymes, and markers of cellular oxidative stress were assessed. The concentration of the sperm per milliliter of epididymal washed fluid, sperm motility, serum testosterone, plasma insulin levels, lipid, and metabolic toxicity sensors were also measured. Significant amelioration (p ˂ 0.05) of the negatively deviated above-mentioned parameters and the disrupted histomorphology of testicles towards vehicle-treated control were noted after uninterrupted 28 days of treatment to diabetic rats with the mentioned extracts of Aloe vera (L.). The highest percentage of recovery in the adopted sensors was noted in the hydro-ethanol extract-treated diabetes group than others. Hydro-ethanol extract of the said plant part is potent among all other extracts for correcting such hypo-function of testicles in diabetes.